Pengaruh Ketingian Terhadap Diameter Polen Lebah Madu (Apis Cerana) Di Kabupaten Malang - Muhammad Jayuli; Muhammad Junus; Wahju Nursita (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2018)
Bees use pollen as a source of protein to support life and to increase the productivity. The size and type of pollen carried by bees are very diverse. Plants in high altitudes may produce pollen of different diameters than those in low altitudes. It is necessary to measure pollen diameter from different plants to know the honeybees’ preferred food source. The purpose of this research was to determine the effect of altitude on pollen diameter from various types of plants carried by bees to increase honey production. This was done by performing field experiments. The design used for this experiment was the completely randomized linear model with three altitude treatments, which were 0-100 m asl (P1), 400-499 m asl (P2) and 800-899 m asl (P3). The results show that altitude has a significant effect (P<0.01) on honeybee Apis cerana pollen diameter. The equatorial and polar pollen diameter was reached by P2 wich was 42.1 ± 4.69 µm and 49.0 ± 4.98 µm, respect highly. Where as the smallest equatorial and polar pollen diameter was reached by P1 wich was 21.1 ± 1.45 µm and 27.0 ± 2.64 µm. To fulfill pollen needs, Apis cerana bees do not necessarily depend on specific pollen diameters. These bees are taking pollens with equatorial diameter of 8.52 μm to 93.68 µm and dan polar diameter polen 8.93 µm to 97.99 µm.